2021
DOI: 10.3390/ijms22063018
|View full text |Cite
|
Sign up to set email alerts
|

Chromatography-Independent Fractionation and Newly Identified Molecular Features of the Adzuki Bean (Vigna angularis Willd.) β-vignin Protein

Abstract: Adzuki seed β-vignin, a vicilin-like globulin, has proven to exert various health-promoting biological activities, notably in cardiovascular health. A simple scalable enrichment procedure of this protein for further nutritional and functional studies is crucial. In this study, a simplified chromatography-independent protein fractionation procedure has been optimized and described. The electrophoretic analysis showed a high degree of homogeneity of β-vignin isolate. Furthermore, the molecular features of the pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…β-Conglycinin is the vicilin storage protein of soybean, and it was evaluated to have multiple health benefits including modulating lipid accumulation and reducing risk of obesity and nonalcoholic fatty liver disease as reviewed by [40]. Vicilin is also present in other legumes such as mung bean, cowpea, and adzuki bean with increasing interest in its potential health benefits [41][42][43]. One study [42] found that β-vignin, a vicilin-like protein from adzuki bean, was able to reduce the activation of IL-8 to basal level [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…β-Conglycinin is the vicilin storage protein of soybean, and it was evaluated to have multiple health benefits including modulating lipid accumulation and reducing risk of obesity and nonalcoholic fatty liver disease as reviewed by [40]. Vicilin is also present in other legumes such as mung bean, cowpea, and adzuki bean with increasing interest in its potential health benefits [41][42][43]. One study [42] found that β-vignin, a vicilin-like protein from adzuki bean, was able to reduce the activation of IL-8 to basal level [42].…”
Section: Discussionmentioning
confidence: 99%
“…Vicilin is also present in other legumes such as mung bean, cowpea, and adzuki bean with increasing interest in its potential health benefits [41][42][43]. One study [42] found that β-vignin, a vicilin-like protein from adzuki bean, was able to reduce the activation of IL-8 to basal level [42]. Therefore, β-conglycinin from the SCD samples potentially contributed to anti-inflammation through the inhibition of the NF-κB signaling pathway and inhibition of inflammation-related enzymes as was shown in the correlations.…”
Section: Discussionmentioning
confidence: 99%
“…Adzuki bean protein content is at par with other pulses like chickpea (21.5 g/100 g), green gram (22.5 g/100 g), black gram (21.9 g/100 g), and peas (20.4 g/100 g) [45]. Additionally, adzuki bean protein also possesses other known health-promoting properties, such as ACE inhibitory activity (a substance that narrows blood vessels) and anti-inflammatory properties [46,47]. Adzuki beans can be integrated with climate resilience, organic farming, multi-cropping, low carbon and water footprint, and sustainable food production systems.…”
Section: Total Protein Contentmentioning
confidence: 99%
“…The adzuki bean protein was predominated by vicilin‐like (7S) globulin (about 78%), whereas the legumin‐like (11S) globulin only accounts for nearly 12% (Meng & Ma, 2001). Adzuki bean β‐vignin, the 7S globulin with multiple health benefits, had high in vitro digestibility (91%) as measured by pepsin and pancreatin (Philadelpho et al., 2021). The protein efficiency ratio of adzuki bean protein was close to 3, which suggested its good nutritional value and digestibility (Ge, Sun, et al., 2021).…”
Section: Chemical Compositions and Their Propertiesmentioning
confidence: 99%
“…Adzuki bean extracts and isolates also show anti‐inflammatory effects in vitro and in vivo. Cellular studies indicated the anti‐inflammatory effects of the adzuki bean isolates, such as β‐vignin protein, saponins, and terpenoids, were suggested by the inhibition of interleukin (IL)−8 and nitric oxide production (Jiang et al., 2014; Philadelpho et al., 2021). In animal studies, red (Kim et al., 2019) and black (Yook et al., 2017) adzuki bean extracts inhibited the production of pro‐inflammatory transcription factors, such as tumor necrosis factor (TNF)‐α, IL‐1, and IL‐6, via the suppression of nuclear factor kappa light chain enhancer of activated B cells (NF‐κB).…”
Section: Health Benefits Of Adzuki Bean and Its Componentsmentioning
confidence: 99%